Paradoxical action of zolpidem: interplay between dysregulation of the synergetic actions of γ-aminobutyric acid type A receptors and neuronal cotransporters (KCC2/NKCC1) - Che Has, Ahmad Tarmizi; Mohamad, Fatin H; Othman, Muhammad Zulfadhli; Abd Halim, Khairul Bariyyah (Taylor and Francis, 2025)
Zolpidem, or commercially known as Ambien or Stilnox, is a sedative-hypnotic agent, which is usually prescribed to manage sleeping difficulties in individuals with insomnia. The site of its sedative-hypnotic action is the γ-aminobutyric acid type A receptor, which it shares with benzodiazepines. However, this substance has been consistently associated to awaken patients with brain injuries such as trauma, stroke, disorders of consciousness and has also been expanded to the recovery of brain function in the event of hypoxic damage, cerebrovascular ischemic injury, infection of the central nervous system, toxins and poisoning, degenerative diseases, tumors, and congenital disorders. Aside from that, the effect has been observed in a wide spectrum of neurological diseases, from movement disorders such as Parkinson's disease and dystonia to neurological deficits and anaphylactic hypoxia. The wide spectrum of injuries and disorders reported poses a challenge in investigating the exact mechanisms of action underlying the awakening effect. Therefore, the main question is how it is possible for a substance originally intended as a sedative-hypnotic agent to induce an awakening effect? In this review, we discuss the synergetic roles of GABAA receptors, which are the target receptor for zolpidem, along with neuronal cation-Cl- co-transporters KCC2/NKCC1 in regulating the inhibitory nature of the GABAergic transmission in brain injury, which might explain the awakening effect of zolpidem in brain injuries